Sikap Konsumen serta Faktor-faktor yang Memengaruhi Pola Konsumsi dan Pengeluaran Konsumen Produk Olahan Ayam Beku di Kota Metro - Thooriq, Naqiyya Amaniya; Indriani, Yaktiworo; Affandi, Muhammad Irfan (Universitas Galuh, 2025)
This research aims to analyze (1) the decision-making process in purchasing frozen processed chicken products in Metro City, (2) consumer attitudes towards frozen processed chicken products in Metro City, (3) the factors influencing consumption patterns of frozen processed chicken products in Metro City, and (4) the factors affecting expenditures on frozen processed chicken in Metro City. The method used is survey, approvead by descriptive qualitative and quantitative approach with a sample of 100 respondents. Data collection was conducted using an online questionnaire in February in Metro City, which was determined purposively, and analyzed using the Fishbein multi-attribute model, descriptive analysis, factor analysis, and multiple linear regression. The research results indicate that (1) the attributes most considered by consumers are taste, nutritional content, and type of product. (2) Consumption patterns are influenced by the types of products frequently consumed, consumer spending on frozen chicken processed meat, the amount consumed, where the products are purchased, the quantity of main meals consumed in a day, preparation methods, frozen chicken processed meat as side dishes, and frozen chicken processed meat as snacks. (3) The factors determining the consumption pattern of frozen chicken processed products in Metro City are formed based on two main components according to the leading factor values. The first component (product attributes) consists of price (X1), brand (X2), packaging design (X4), and texture (X5). The second component (marketing appeal) consists of ease of access (X3) and promotions (X6). (4) Factors that influence expenditure are the number of family members (X2), purchasing frequency (X3) and brand (D3), while income (X1), age (X4), taste (D1), wife's education level (D2), price (D4) and wife's job (D5) do not have a significant influence on expenditure on frozen chicken meat products in Metro City.